Anti-lipoapoptotic effects of Alisma orientalis extract on non-esterified fatty acid-induced HepG2 cells. Issue 1 (December 2016) - Jeong, Hyeon-Soo; Cho, Young-Hwan; Kim, Kang-Hoon; Kim, Yumi; Kim, Ki-Suk; Na, Yun-Cheol; Park, Jiyoung; Lee, In-Seung; Lee, Jang-Hoon; Jang, Hyeung-Jin
Abstract Background Liver steatosis was caused by lipid accumulation in the liver.Alisma orientale (AO) is recognized as a promising candidate with therapeutic efficacy for the treatment of nonalcoholic fatty liver disease (NAFLD). HepG2 hepatocyte cell line is commonly used for liver disease cell model. Method The HepG2 cells were cultured with the NEFAs mixture (oleic and palmitic acids, 2:1 ratio) for 24 h to induce hepatic steatosis. Then different doses ofAlisma orientale extract (AOE) was treated to HepG2 for 24 h. Incubated cells were used for further experiments. Results The AOE showed inhibitory effects on lipid accumulation in the Oil Red O staining and Nile red staining tests with no cytotoxicity at a concentration of 300 μg/mL. Fatty acid synthase (FASN) and acetyl-CoA carboxylase 1 (ACC1) mRNA and protein expression level were down-regulated after AOE treatment. Bcl-2 associated X protein (Bax) and c-Jun N-terminal kinase (JNK) mRNA expression level were decreased as well as p-JNK (activated form of JNK), Bax, cleaved caspase-9, caspase-3 protein expression level. Anti-apopototic B-cell lymphoma 2 (Bcl-2) protein level increased after AOE treatment. In addition, inflammatory protein expression including p-p65, p65, COX-2 and iNOS were inhibited by AOE treatment. Conclusion The results suggest that AOE has anti-steatosis effects that involve lipogenesis, anti-lipoapoptosis, and anti-inflammation in the NEFA-induced NAFLD pathological cell model.